Mematuhi Protokol Kesehatan di Masa Pandemi Covid-19 Menurut Pandangan Fiqh Sosial Kiai Sahal - Janah, Tutik Nurul (JURNAL AT-TURAS, 2021)
This study is qualitative research. This research uses descriptive methods. Analysis of the data in this study uses the perspective of fiqh social. Health protocol is an effort to maintain health during the COVID-19 pandemic. Health protocols include three main elements: prevention, detection, and response.In the perspective of social fiqh, adhering to health protocols during the COVID-19 pandemic is an inevitability.  This opinion refers to the development of examples of qaidah fiqhiyyah on the use of madzhab qauli in the methodology of fiqh social. The fiqh social perspective considers that complying with health protocols is part of hifdz al nafs.Therefore, matters related to hifdz al nafs, must also be implemented in order to achieve maqasid al sharia. In this case, including in complying with health protocols during the COVID-19 pandemic.